ANALISIS PEMAHAMAN KONSEP CALON GURU SEKOLAH DASAR PADA KONSEP PENCERNAAN - Andayani; Rif’at Shafwatul Anam; Monika Handayani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article provides an overview of the understanding of prospective elementary school teachers regarding the digestive concept. The research described in this article is descriptive research with a survey type, which was delivered to 105 elementary school teacher candidates. The instruments distributed were conducted online in the form of multiple choices related to the concept of digestion and a questionnaire related to their learning experiences. Based on the results, it was found that, in general, the answers given by prospective teachers were not in line with expectations. It is proven by the average percentage of correct answers of 45.12%, which was categorized in the "Less" category. In addition, most of the respondents' learning experiences on the concept of digestion came from more miniature interactive books, visualization, and packaging of concepts that were deemed not to be following what they needed. It means that the need for teaching materials/media development to ease the teachers to understand the concept of digestion. One solution to overcome this was to use Augmented Reality (AR) media. The media combines technology to present the content learned on gadgets in terms of the real-world environment. In addition to its making, it is necessary to pay attention to the pedagogical aspects so that the concepts given in the media are easy for users to learn.